Chemokine Heterocomplexes and Cancer: A Novel Chapter to Be Written in Tumor Immunity - D'Agostino, Gianluca; Cecchinato, Valentina; Uguccioni, Mariagrazia (Frontiers in Immunology, 2018)
Infiltrating immune cells are a key component of the tumor microenvironment and play central roles in dictating tumor fate, either promoting anti-tumor immune responses, or sustaining tumor growth, angiogenesis and metastasis. A distinctive microenvironment is often associated to different tumor types, with substantial differences in prognosis. The production of a variety of chemotactic factors by cancer and stromal cells orchestrates cell recruitment, local immune responses or cancer progression. In the last decades, different studies have highlighted how chemotactic cues, and in particular chemokines, can act as natural antagonists or induce synergistic effects on selective receptors by forming heterocomplexes, thus shaping migratory responses of immune cells. A variety of chemokines has been described to be able to form heterocomplexes both in vitro and in vivo under inflammatory conditions, but nowadays little is known on the presence and relevance of heterocomplexes in the tumor microenvironment. In recent years, the alarmin HMGB1, which can be massively released within the tumor microenvironment, has also been described to form a complex with the chemokine CXCL12 enhancing CXCR4-mediated signaling, thus providing an additional regulation of the activity of the chemokine system. In the present review, we will discuss the current knowledge on the synergy occurring between chemokines or inflammatory molecules, and describe the multiple functions exerted by the chemokines expressed in the tumor microenvironment, pointing our attention to the synergism as a possible modulator of tumor suppression or progression.